Schemele de împădurire dese şi stabilitatea monoculturilor de molid – este posibilă realizarea unui echilibru de durată? [Narrow spacing and stability of Norway spruce monocultures - is a long-term equilibrium possible?] - Nicolescu N.-V; Petrițan I.-C; Vasilescu M.-M; Ferreira P; Henriques S (Bucovina Forestieră, 2003)
Norway spruce (Picea abies (L.) Karst) - one of the most important forest species in both Europe (about 34 million ha) and Romania (about 1.4 million ha) - has been highly expanded in monocultures outside of its natural range since mid- 19th century. Unfortunately, despite their many advantages (easy establishment, quick growth, high production, multiple uses of timber etc.), Norway spruce pure stands are facing many problems being especially subjected to wind and snow damages. Taking into account these facts, the article outlines the most important factors influencing Norway spruce stand stability such as initial spacing (stocking) and early silvicultural interventions. It seems obvious that two solutions for a better stability to snow damages at early ages exists: low stocking (wide spacing) at planting (maximum 2,000-2,500 plants per ha) and high stocking (narrow spacing) at planting (4,000-5,000 plants per ha) but followed by high intensity cleaningrespacing started no later than end of saplingbeginning of thicket stage. Under present Romanian conditions, facing many economic constraints (e.g., high cost of planting and tending; lack of labour force), the solution of low stocking (wide spacing) at planting as already stated at the beginning of 1980’s but never applied on a large scale seems more feasible and realistic